Boerhaave's syndrome complicated by a Saccharomyces cerevisiae pleural empyema. Case report and review of the literature. Issue 5 (3rd September 2018) - Teblick, Arno; Jansens, Hilde; Dams, Karolien; Somville, Francis J.; Jorens, Philippe G.
Abstract: Objective and Importance Boerhaave's syndrome is a sudden and rare form of oesophageal rupture and is often complicated by local or systemic infection of the mediastinum or pleural cavity. Several micro-organisms are documented as cause of pleural empyema in patients with Boerhaave's syndrome. Intervention (& Technique) We report on a previously healthy 74-year-old male who was admitted at a regional hospital with severe retrosternal and abdominal pain after an episode of vigorous vomiting the morning after ingestion of large quantity of beer. A CT-scan confirmed the diagnosis of Boerhaave's syndrome, an oesophageal stent was placed and a left-sided pleural empyema necessitated chest tube drainage. Pleural fluid samples were cultured every two days and were positive for Proteus mirabilis on day 2 after admission and for Saccharomyces cerevisiae on day 8 after admission. Intravenous fluconazole 800 mg per day was added to the antibacterial treatment. Pleural fluid culture became negative for P. mirabilis on day 23 and for S. cerevisiae on day 13. Recurrent empyema necessitated intrapleural thrombolysis. The patient could be discharged from the ICU after 43 days, from the normal ward to a rehabilitation centre after an additional 13 days. Conclusion Pleural empyema caused by S. cerevisiae, commonly known as 'Brewers' yeast', has never been described in such patients. Our case illustrates that clinicians should be aware of infection with S. cerevisiae after oesophageal perforation, soon after ingestion of beer. Adequate antimycotic treatment was successful and led to negative culture of pleural fluid after 5 days.